2002
DOI: 10.1177/154411130201300203
|View full text |Cite
|
Sign up to set email alerts
|

Do We Need to be Concerned about Dental Caries in the Coming Millennium?

Abstract: ABSTRACT:Dental caries continues to be a pubic health problem despite claims that 50% of schoolchildren are caries-free. There are widespread variations in the prevalence of caries worldwide. Caries lesions are the clinical manifestation of a pathogenic process that may have been occurring on the tooth surface for months or years. Acid production by bacteria embedded in a biofilm termed "dental plaque" is a key aspect of the pathogenesis of dental caries; nevertheless, the ability of micro-organisms to survive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
109
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 201 publications
(115 citation statements)
references
References 56 publications
(64 reference statements)
2
109
0
3
Order By: Relevance
“…S. mutans can utilize dietary sucrose to synthesize EPSs through Gtfs, adheres to the tooth surface (Bowen 2002), and secretes at least three types of Gtfs-GtfB, GtfC, and GtfD-which are encoded by gtfB, gtfC, and gtfD, respectively (Terao et al 2009). GtfB, with a molecular weight (MW) of 165.8 kDa, catalyzes the synthesis of water-insoluble, 1,3-linked glucan; GtfC has a molecular weight of 153.0 kDa and forms a water-soluble, 1,6-linked glucan and a water-insoluble, 1,3-linked glucan polymer, while GtfD, with a molecular weight of 163.4 kDa, synthesizes a watersoluble, 1,6-linked glucan (Hanada and Kuramitsu 1988;Hanada and Kuramitsu 1989;Kopec et al 1997).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…S. mutans can utilize dietary sucrose to synthesize EPSs through Gtfs, adheres to the tooth surface (Bowen 2002), and secretes at least three types of Gtfs-GtfB, GtfC, and GtfD-which are encoded by gtfB, gtfC, and gtfD, respectively (Terao et al 2009). GtfB, with a molecular weight (MW) of 165.8 kDa, catalyzes the synthesis of water-insoluble, 1,3-linked glucan; GtfC has a molecular weight of 153.0 kDa and forms a water-soluble, 1,6-linked glucan and a water-insoluble, 1,3-linked glucan polymer, while GtfD, with a molecular weight of 163.4 kDa, synthesizes a watersoluble, 1,6-linked glucan (Hanada and Kuramitsu 1988;Hanada and Kuramitsu 1989;Kopec et al 1997).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…However, there is no direct relationship between the exposure to sugars and the MS counts in dental plaque (6)(7)(8), suggesting that the changes induced by these microorganisms in dental biofilm are more important than their levels (6). Thus, EPS have been considered virulence factors of the bacteria present in dental biofilm (9) and it has been shown that caries incidence might be more related to the capacity of specific S. mutans strains to synthesize insoluble EPS than to their proportions in dental biofilm (10). Therefore, some studies have shown that the oral cavity may present distinct genotypes of S. mutans, not only in saliva but also in dental biofilm (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Among them, dental caries continues to be the single most prevalent and costly oral infectious disease (Marsh, 2003;Dye et al, 2007). Dental caries results from the interaction of specific bacteria with constituents of the diet within a dental biofilm known as plaque (Bowen, 2002). Sucrose is considered to be the "arch criminal" from the dietary aspect because it serves as a substrate for synthesis of extracellular (EPS) and intracellular (IPS) polysaccharides in dental biofilm and is also fermentable (Bowen, 2002).…”
mentioning
confidence: 99%